The unfolding turmoil of 2007 - 2008: Lessons and responses - Ben Cohen; Eli Remolona (Asian Development Bank Institute (ADBI), 2008)
While the unfolding financial turmoil has involved new elements, more fundamental elements have remained the same. New elements include structured credit, the originate-to-distribute business model and the tri-party repurchase agreement. The recurrence of crises reflects a basic procyclicality in the system, which is characterized by a build-up of risk-taking and leverage in good times and an abrupt withdrawal from risk and an unwinding of leverage in bad times. To deal with the adverse liquidity spiral that has characterized the current crisis, central banks have tried to strike a balance between the importance of the continued availability of market liquidity as a public good and the moral hazard that any market intervention may induce. In proposing long-term responses to the crisis, the Financial Stability Forum has focused on areas where incentives for risk-taking may be aligned more properly and areas where risk management may be made more robust. Nonetheless a recognition that the procyclicality of the system lies at the root of the crisis would suggest more aggressive countercyclical measures are needed.
Keywords: E32; E44; E58; G14; G18; G21; G24; G28; 330